Experimental Investigation of Dry Friction Damping and Cubic Stiffness Non-Linearity - Stanbridge, Anthony B.; Ewins, David J.; Sanliturk, Kenan Y.; Ferreira, Janito V. (American Society of Mechanical Engineers, 2001)
Abstract Experimental vibration techniques used in the characterisation of the two most common types of non-linear structure are described here. The first is used to determine friction contact hysteresis loops to provide data which can be incorporated into large, otherwise linear, structural models, to predict non-linear vibration responses. The second is a method of measuring frequency response functions (FRFs) of structures with non-linear, amplitude-dependent stiffness and damping, including the ‘unstable’, overhanging part of the FRF curve, by using a controlled-amplitude, stepped-frequency sinusoidal input. These apparently rather different test techniques are in fact connected by the fact that, in order to be effective, they both require an additional mass to be installed, on the input side of the force transducer.